Dynamic resistance of a high-Tc coated conductor wire in a perpendicular magnetic field at 77 K. (17th January 2017) - Jiang, Zhenan; Toyomoto, Ryuki; Amemiya, Naoyuki; Zhang, Xingyou; Bumby, Chris W
Abstract: Superconducting high- T c coated conductor (CC) wires comprise a ceramic thin film with a large aspect ratio. This geometry can lead to significant dissipative losses when exposed to an alternating magnetic field. Here we report experimental measurements of the 'dynamic resistance' of commercially available SuperPower and Fujikura CC wires in an AC perpendicular field. The onset of dynamic resistance occurs at a threshold field amplitude, which is determined by the total DC transport current and the penetration field of the conductor. We show that the field-dependence of the normalised magnetisation loss provides an unambiguous value for this threshold field at zero transport current. From this insight we then obtain an expression for the dynamic resistance in perpendicular field. This approach implies a linear relationship between dynamic resistance and applied field amplitude, and also between threshold field and transport current and this is consistent with our experimental data. The analytical expression obtained yields values that closely agree with measurements obtained across a wide range of frequencies and transport currents, and for multiple CC wires produced by different wire manufacturers and with significantly differing dimensions and critical currents. We further show that at high transport currents, the measured DC resistance includes an additional nonlinear term which is due to flux-flow resistance incurred by the DC transport current. This occurs once the field-dependent critical current of the wire falls below the DC transport current for part of each field cycle. Our results provide an effective and simple approach to calculating the dynamic resistance of a CC wire, at current and field magnitudes consistent with those expected in superconducting machines.